Interaction Studies of Bis-(p-aminobenzoato)diaquanickel(II) and Bis-(p-aminobenzoato) triaquacadmium(II) Complexes with Cat Genomic DNA - ARSLANTAS, ALI; SOZMEN, MAHMUT; NECEFOGLU, HACALI (Asian Journal of Chemistry, 2010)
Bis-(p-aminobenzoato)diaquanickel(II) [Ni(p-H2N-C6H4COO)2· 2H2O] and bis-(p-aminobenzoato)triaquacadmium(II) [Cd(p-H2NC6H4COO) 2·3H2O] complexes derived from p-aminobenzoate are reported. The genomic DNA interactions of these complexes with cat genomic DNA have been investigated with UV spectroscopy, gel electrophoresis and viscosity measurements. Ni(H2N-C6H4COO)2·2H2O and Cd(H2NC6H4COO) 2·3H2Ocomplexes exhibit interaction activities with DNA. The experimental results indicate that the complexes can bind to DNA via an intercalative mode. The intrinsic binding constants of the complexes with genomic DNA are 5.2 × 105 - 2.49 × 105 M-1, respectively.